Islamic philanthropy and the private sector in Indonesia - Hilman Latief (IAIN Salatiga, 2013)
This paper investigates the growing initiatives within the private sector to orga-nize social welfare activities, and analyzes the way in which zakat (alms) is prac-ticed among Muslim businessmen. The establishment of zakat agencies withinprivate companies has marked the latest trend of the practice of philanthropy inIndonesia. Corporation-based zakat collectors have become new players in therapid growth of the Indonesia’s zakat sector in the past two decades. This paperexamines the following issues: what are the main forces stimulating corpora-tions to set up zakat collectors; what kinds of religious ideas are applied to mo-bilize charities from Muslim workers, and how these concepts are interpretedand practiced within private companies? This paper argues that the inception ofa new concept in zakat practice, such as zakat on corporate wealth, has indi-cated the dynamics process of Islamization of the private sector in Indonesia.Tulisan ini meneliti inisiatif yang tumbuh dalam sektor swasta untuk mengaturkegiatan kesejahteraan sosial, dan menganalisa cara di mana zakat (sedekah)dipraktekkan di kalangan pengusaha Muslim. Pembentukan lembaga-lembagazakat dalam perusahaan swasta telah menandai tren terbaru dari praktek filantropidi Indonesia. Perusahaan berbasis kolektor zakat telah menjadi pemain barudalam pertumbuhan yang cepat dari sektor zakat Indonesia dalam dua dekadeterakhir. Makalah ini membahas isu-isu berikut: apa kekuatan utama merangsang perusahaan untuk mendirikan kolektor zakat, apa jenis ide-ide keagamaan yangditerapkan untuk memobilisasi amal dari para pekerja Muslim, dan bagaimanakonsep-konsep ini ditafsirkan dan dipraktekkan dalam perusahaan swasta? Makalahini berpendapat bahwa lahirnya konsep baru dalam praktek zakat, seperti zakatpada kekayaan perusahaan, telah menunjukkan proses dinamika Islamisasi sektorswasta di Indonesia.